Parameter Sensitivity Analysis of an Induction Motor (Hungarian Journal of Industry and Chemistry, 2011)
A simple dynamic model of an induction motor is presented in this paper based on engineering principles that describe the mechanical phenomena together with the electrical model. The investigated state space model consists of nonlinear state equations and linear output equations. The model has been verified under the usual controlled operating conditions when the speed is controlled. The effect of load on the controlled induction motor has been analyzed by simulation. The sensitivity analysis of the induction motor and the bridge of the inverter have been applied to determine the model parameters to be estimated.